Metal and Machine MSMES Penetrate The International Market: Case Study On MSMES. Andi Welder, West Nusa Tenggara - Muhammad Zainuddin; Sudarmiatin Sudarmiatin; Rozmiza Bidin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Objective: This study aims to reveal the strategies used by Metal and Machinery MSMEs in West Nusa Tenggara in competing and expanding their products to foreign markets or international markets. Design/methodology/study approach: The method used in this study is research with a case study method with interviews at MSMEs Andi Welder who process metals and produce coffee processing equipment. Conclusion: MSMEs Andi Welder uses Canva's analysis strategy in innovating its products which aims to see the market response of what products are most sought after by consumers then the products are refined so that they can be accepted by the international market. Limitations/implications of research – This research can not only limit the product innovation strategies that are acceptable to consumers, then for future research can expand on other strategies such as brand strategy and product quality. Originality/value: This research is a case study research that raises the strategy of metal and machinery MSMEs to enter the international market